The Effectiveness of Dokterkit Application-Based Coronary Heart Risk Monitoring and Education - Atmadjaja, Agnes; Wartiningsih, Minarni; Sasono, Bimo (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: In 2019, primary diagnoses in coronary heart disease outpatients increased by 1.4% and secondary diagnoses byi6% of patients. Aims: To determine the effectiveness of Edmon (Education & Monitoring) based on the medical kit application on coronary heart disease risk control at Soewandhi Hospital Surabaya. Method: This study is a quantitative study with quasi-experimental non-equivalent group design. This study involved 30 people consistingi of 2 groups (the treatment group that received CHD health education through a dokterkit application and through leaflets). This research was conducted at Soewandi Hospital in Surabaya in August-November 2022. Univariate data analysis techniques were performed on each variable from the research results, then an independenti test was carried out to find out the differencesi betweeni the two groups. Results: The results showed that android-based education and monitoring were effective because they contributed to a 26.7% reductioni in the numberi of patientsi with severe CHD risk and a 40% increase in the numberi of patients with normal urici acidi levelsi in the treatment group. Conclusion: Dokterkit-based education & monitoring is effective in controlling the risk of coronaryi heart diseasei and uric acid levelsi in Soewandhie Hospital Surabaya, but not effective in reducing cholesterol levels, systolic blood pressure, blood sugar levels and not effective in changing smoking behavior.